Legal Construction of International Business Contracts as an Instrument for Strengthening Banana Cracker Exports and Ogan Banana Supply Chain Management in Lumajang Regency - Ratnaningsih; Sudjatmiko; Hastuti, Sri; Maulidandi, Muhammad Akmal Naufaldi (Faculty of Law, Universitas Pasundan, 2025)
Today's entrepreneurs prioritize international trade as an important goal in business development, which leads to the formation of international business contracts, but not all entrepreneurs understand the various regulations related to international business contracts, dispute resolution in the event of a dispute, and legal certainty in the event of force majeure. In addition, this study also wants to analyze the provisions for the use of Indonesian in agreements based on Law of the Republic of Indonesia Number 24 of 2009 concerning the Flag, Language, and National Emblem, as well as the National Anthem, with an analytical knife using the principle of freedom of contact. This research related to international business contracts was inspired by the desires of home industry entrepreneurs in Nogosari Village, Rowokangkung District, Lumajang Regency, who produce